Теоретичні аспекти формування антикризової стійкості сільськогосподарських підприємств - Вініченко, Ігор Іванович; Vinichenko, Ihor; Комська, М. М.; Komska, M. (Дніпровський державний аграрно-економічний університет, 2021)
Визначено, що для більшості сільськогосподарських підприємств важливим тактичними завданнями їх розвитку є недопущення банкрутства в довгостроковій перспективі. Тому особливого значення за умов сьогодення набуває формування ефективного механізму управління підприємством, заснованого на аналізі його фінансово-економічного стану. Встановлено, що серед типових ознак кризового стану підприємства науковці визначають наступні: зниження рентабельності діяльності підприємства, кредитні ресурси використовуються в основному на погашення відсотків та повернення раніше отриманих кредитів, значно частіше виникають несприятливі виробничі ситуації, порушується ритмічність постачання сировини та готової продукції, виникає некерований стан розвитку підприємства і будь-яка несприятлива подія здатна створити реальну загрозу його банкрутства. За результатами дослідження визначено основні методи формування антикризової стійкості підприємств: методи посилення фінансової стійкості за рахунок управління ліквідністю та структурою активів і джерел їх фінансування; управління собівартістю виробництва продукції за рахунок оптимізації постійних і змінних витрат; управління доходами підприємства за основним видом діяльності та позареалізаційними доходами; антикризового управління персоналом. It is determined that for most agricultural enterprises an important tactical task of their development is to prevent bankruptcy in the end. Therefore, of particular importance in today's conditions is the formation of an effective mechanism for managing the enterprise, based on the analysis of its financial and economic condition. It is established that among the typical signs of the crisis of the enterprise, scientists identify the following: reduced profitability, credit resources are used mainly to repay interest and repay previously obtained loans, much more often there are unfavorable production situations, disrupted supply of raw materials and finished products, uncontrolled enterprise development and any adverse events can create a real threat of bankruptcy. We believe that the crisis management — it is government policy that aims to protect economic agents from crises and prevent their bankruptcy. It is carried out at the meso and macro levels and is a system of political, legal, financial, and economic measures. For crisis management requires certain information database, creating specific research methodology, highly skilled professionals, research and development, adoption and implementation of stabilization measures of the national economy. The analysis offers its own definition of a crisis. Crisis — an event that affects the sustainability of economic development of the enterprise and is characterized by a set of reasons for its occurrence and specific consequences of the manifestation, which requires financial and economic analysis to make management decisions in the shortest possible time. We believe that anti-crisis resilience should be understand as the company's ability to prevent significant impact of the crisis on its financial and economic activities with crisis management technology, industry specifics and the formation of reserve funds during the recovery phase of the enterprise life cycle. According to the results of the study, the main methods of formation of anti-crisis stability of enterprises are determined: methods of strengthening financial stability by managing liquidity and the structure of assets and sources of their financing; managing the cost of production by optimizing fixed and variable costs; enterprise income management by main activity and non-operating income; anti-crisis personnel management.
Theoretical aspects of formation of anti-crisis stability of agricultural enterprises
Keywords: антикризова стійкість; аnti-crisis resilience; антикризове управління; crisis management; банкрутство; bankruptcy; державне регулювання; government regulation; криза; crisis; сільськогосподарські підприємства; agricultural enterprises; соціально-економічна система; socio-economic system